Integrasi Blockchain dan Keamanan Data untuk Meningkatkan Efisiensi dan Transparansi Sistem Logistik Global - Cheysha Restu Nabila; Rissal Efendi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
The global logistics system currently faces complex challenges related to efficiency and transparency. To address these issues, integrating blockchain and data security has emerged as a promising solution. Blockchain, the foundational technology behind cryptocurrencies, provides the capability to record, verify, and secure transactions in a decentralized and transparent manner. This study aims to analyze the potential of integrating blockchain and data security to enhance efficiency and transparency in global logistics systems. The research employs a literature review approach, examining relevant studies on blockchain and data security applications within the global logistics context. The findings indicate that blockchain integration in global logistics can facilitate a more efficient supply chain by enabling transparency, real-time validation, and enhanced monitoring of logistics activities. Additionally, encrypted data security can mitigate security risks and reduce fraud, providing better protection against cyberattacks and data manipulation.